The Quest for Representative Juries in the Northwest Territories - Davison, Charles B. (Northern Review, 2020)
[From Introduction]Inherent in our constitutional right to a jury trial in criminal cases—for offences where imprisonment for five years or more is a possible sentence— is the right to have jurors who are our “peers” and “equals.” This right can be traced back to 1215 when King John signed the Magna Carta to make peace with the wealthy men of England.The route from the Magna Carta to Canadian criminal law in the early twenty-first century is long and convoluted, and extra twists and turns are added when we consider the use of juries in Canada’s North. Here, where the effects of colonialism are still felt on a daily basis, and where communities from which a jury might be drawn sometimes number only a few hundred persons, the ability to obtain a jury comprised of “the peers” of our clients, who are usually Indigenous, can be challenging and sometimes difficult. In this article I offer my perspective, as a practising criminal defence lawyer in the Northwest Territories, on the challenges we face in trying to obtain juries that truly represent the communities from which our clients originate. ... ...More